A Survey of Education of Early Colonial Hong Kong - Chan, Hugo Wai Hoo; Lo, Noble Po Kan; Tso, Anna Wing Bo; Ma, Beatrice Kuen Fong (Journal of Posthumanism, 2026)
This paper explores the evolution of education during the early colonial period in Hong Kong, focusing on the coexistence and influence of traditional Chinese and Western educational philosophies. It examines two key institutions: the Kun Ting Study Hall, a traditional village school preparing students for the Qing Dynasty's Imperial Civil Service Exam, and St. Paul’s College, a Christian school established to instill Western values and Christian principles. The study highlights their contrasting purposes, with Kun Ting preserving ancestral traditions and St. Paul’s promoting Western ideologies. Over time, both institutions evolved to serve as platforms for elite education and cultural interaction, bridging gaps between the British and local Chinese communities. The paper discusses the role of education in fostering social harmony and shaping colonial Hong Kong’s society. It underscores the enduring significance of these institutions in promoting cross-cultural understanding and influencing Hong Kong’s educational development.